HOW DETECT FRAUD WITH HEXAGON MODEL ON FINANCIAL STATEMENT FRAUD IN PROPERTY AND REAL ESTATE INDONESIA - Hakim, Mohamad Zulman; Hesty Erviani Zulaecha; Kimsen; Eldi Efriadi; Aura Putri Rahmawati; Hesti Febriatul Lubnaningtyas (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Examining how Freud's hexagon framework relates to financial statement fraud is the focus of this study. In total, ten factors were considered. Financial Target, Financial Stability, External Pressure, Change of Director, Nature of Industry, CEO Picture, Political Connection, Audit Opinion, CEO Education and Effective Monitoring. Financial statement fraud is measured using the Beneish M-Score Model. The research sample consists of industries in the property and real estate sector based on data from the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The number of companies included in the sample was 35. This study uses panel data regression analysis for data analysis purposes. The results of this study indicate that Financial Target, Financial Stability, External Pressure, Change of Director, Nature of Industry, CEOPicture Audit Opinion and Effective Monitoring have no effect on the potential for fraudulent financial statements. While Change In Auditor and Political Connection have an effect on fraudulent financial statements in the Property and Real Estate sector.